Electrophoretic coating of LiFePO4/Graphene oxide on carbon fibers as cathode electrodes for structural lithium ion batteries. (26th May 2021) - Sanchez, Jaime S.; Xu, Johanna; Xia, Zhenyuan; Sun, Jinhua; Asp, Leif E.; Palermo, Vincenzo
Abstract: Carbon fibers (CF), commonly used in the structure of airplanes or cars, can also work as conductive electrodes in "structural batteries" for distributed energy storage. To this aim CF should be chemically functionalized, which is challenging due to their complex geometry and surface. Here, we describe an "all-electrostatic" approach taking advantage of the intrinsic conductivity of CF to coat them with a cathode material composed of LiFePO4 blended with nanosheets of electrochemically exfoliated graphene oxide (EGO). We first achieve electrostatic self-assembly of the nanometric components at the nanoscale, then use Electrophoretic Deposition (EPD) to obtain a uniform, macroscale coating on the fibers. We achieve a LiFePO4 loading >90 wt% featuring good adhesion on the carbon fibers, low degradation upon battery cycling, low charge transfer resistance. The electrode composite outperforms similar state-of-the-art cathode materials when used in Half-Cell vs. Li. Full battery cells using coated CF as cathode and pristine CF as anode yield specific energy density of 222.14 Wh⋅kg −1 and power density of 0.29 kW⋅kg −1 with 88.1% capacity retention at 1 C over 300 cycles, compatible with industrial applications of this technique in composites production. Graphical abstract: Image 1